NABARD: An Approach to Agriculture - Sumathy; Das, Akshaya (Jurnal Multidisiplin Madani, 2024)
To estimate the amount of agricultural credit disbursed, the study, which looked at the percentage of term loans in total agriculture by different types of banks, was done. Many secondary sources, including the NABARD annual report, publications from the RBI, and a number of periodicals, were used to compile the study's data. According to the study's findings, term loans accounted for a sizeable share of the credit granted by commercial banks